PFAS levels and exposure determinants in sensitive population groups. (February 2023) - Fábelová, L.; Beneito, A.; Casas, M.; Colles, A.; Dalsager, L.; Den Hond, E.; Dereumeaux, C.; Ferguson, K.; Gilles, L.; Govarts, E.; Irizar, A.; Lopez Espinosa, M.J.; et al.
Abstract: Background: Per- and polyfluoroalkyl substances (PFAS) are persistent organic pollutants. The first exposure to PFAS occurs in utero, after birth it continues via breast milk, food intake, environment, and consumer products that contain these chemicals. Our aim was to identify determinants of PFAS concentrations in sensitive population subgroups– pregnant women and newborns. Methods: Nine European birth cohorts provided exposure data on PFAS in pregnant women (INMA-Gipuzkoa, Sabadell, Valencia, ELFE and MoBa; total N = 5897) or newborns (3xG study, FLEHS 2, FLEHS 3 and PRENATAL; total N = 940). PFOS, PFOA, PFHxS and PFNA concentrations were measured in maternal or cord blood, depending on the cohort (FLEHS 2 measured only PFOS and PFOA). PFAS concentrations were analysed according to maternal characteristics (age, BMI, parity, previous breastfeeding, smoking, and food consumption during pregnancy) and parental educational level. The association between potential determinants and PFAS concentrations was evaluated using multiple linear regression models. Results: We observed significant variations in PFAS concentrations among cohorts. Higher PFAS concentrations were associated with higher maternal age, primipara birth, and educational level, both for maternal blood and cord blood. Higher PFAS concentrations in maternal blood were associated with higher consumption of fish and seafood, meat, offal and eggs. In cord blood, higher PFHxS concentrations were associated with daily meat consumption and higher PFNA with offal consumption. Daily milk and dairy consumption were associated with lower concentrations of PFAS in both, pregnant women and newborns. Conclusion: High detection rates of the four most abundant PFAS demonstrate ubiquitous exposure of sensitive populations, which is of concern. This study identified several determinants of PFAS exposure in pregnant women and newborns, including dietary factors, and these findings can be used for proposing measures to reduce PFAS exposure, particularly from dietary sources. Graphical abstract: Image 1 Highlights: High detection rates of PFAS were observed in the blood of pregnant women and newborns. Higher educational level of father was associated with higher PFAS in cord blood. Dietary factors were associated with PFAS concentrations in pregnant women. Daily milk and dairy consumption was associated with lower PFAS in both populations.